2011
DOI: 10.1111/j.1747-0285.2010.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Docking, Synthesis, and in vitro Evaluation of Antimitotic Estrone Analogs

Abstract: In the present study, Autodock 4.0 was employed to discover potential carbonic anhydrase IX inhibitors that are able to interfere with microtubule dynamics by binding to the Colchicine binding site of tubulin.Modifications at position 2' of estrone were made to include moieties that are known to improve the antimitotic activity of estradiol analogs. 2-ethyl-3-O-sulphamoyl-estra-1,3,5(10),15-tetraen-3-ol-17-one estronem (C9) and 2-ethyl-3-O-sulphamoyl-estra-1,3,5(10)16-tetraene (C12) were synthesized and tested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
171
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(187 citation statements)
references
References 49 publications
16
171
0
Order By: Relevance
“…1a) by modifying the 2′ and 17′ positions with moieties known to improve the anti-mitotic activity and increase the half-life of the compounds [10,11]. This panel was analysed using AutoDockTools4 with the prepare_ligand4py script to determine which compounds bound best with the tubulin colchicine binding site and with carbonic anhydrase IX (CA IX) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) by modifying the 2′ and 17′ positions with moieties known to improve the anti-mitotic activity and increase the half-life of the compounds [10,11]. This panel was analysed using AutoDockTools4 with the prepare_ligand4py script to determine which compounds bound best with the tubulin colchicine binding site and with carbonic anhydrase IX (CA IX) [10].…”
Section: Introductionmentioning
confidence: 99%
“…This panel was analysed using AutoDockTools4 with the prepare_ligand4py script to determine which compounds bound best with the tubulin colchicine binding site and with carbonic anhydrase IX (CA IX) [10]. CA IX is overexpressed in numerous tumour cells, lending a growth advantage to malignant cells within the acidic and hypoxic microenvironment [12]. Selective inhibition of CA IX could potentially be useful in manipulating the extracellular tumour milieu and curtailing metastatic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that ESE-16 was an antimitotic compound and induced apoptosis in these cancer cell lines (Stander et al, 2011;Stander et al, 2012;Nkandue et al, 2013;Stander et al, 2013;Theron et al, 2013). It is important to note that ESE-16 has also been tested on nontumorigenic MCF-12 A breast cells and has shown a higher affinity for cancerous cell lines when compared with this noncancerous cell line (Stander et al, 2012;Stander et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Platelets were exposed to 0.18 μM of ESE-16 (Stander et al, 2011). This concentration was selected as it was previously established that 0.18 μM of ESE-16 inhibited cell growth by 50% (GI 50 ) after 24 h at 37°C (Stander et al, 2011;Stander et al, 2012;Stander et al, 2013).…”
Section: Preparation Of Compoundmentioning
confidence: 99%
“…Inhibitor design based on the estrane core is nonetheless limited, because they must be devoid of estrogenic activity [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%